Penyuluhan Manajemen Seleksi Dan Pencatatan Data Ternak Sapi Pada Kelompok Ternak Iwaq Jaya Farm Di Desa Jango Kecamatan Janapria Kabupaten Lombok Tengah - Eva Amalia Pertiwi; Tapaul Rozi; Muhsinin; Maskur (Universitas Mataram, 2026)
Bali cattle are an endemic Indonesian germplasm known for high reproductive potential and adaptability; however, their genetic quality at the smallholder farmer level has tended to decline due to improper selection management. This community service activity aimed to educate the